Chiral epoxides by desymmetrizing deprotonation of meso-epoxides. - Hodgson, D; Gras, E (2002)
Simple meso-epoxides can be asymmetrically functionalized: Ligand-assisted direct hydrogen-lithium exchange allows the generation of destabilized oxiranyl lithium species and their subsequent trapping by a wide array of electrophiles (see scheme; E = group formed by addition of electrophile). When carried out in the presence of (-)-sparteine as ligand, this reaction provides a new enantioselective route to epoxides.